Linfoma epiteliotrópico multicêntrico em cadela rottweiler: abordagem imaginológica - Souza, João Carlos de (Universidade Federal do Tocantins, 2022)
The Supervised Academic Internship in Imaging Diagnosis of CVU – University Veterinary Clinic of Federal University of Tocantins (EMVZ), in Araguaína, was performed under the guidance of the Professor (Ph.D) Priscilla Macedo de Souza, and supervised by Dr. Flavia Augusta de Oliveira. The Internship took place from May 5th to June 9th, 2021, totaling 295 working hours. The purpose of the report was to collect and describe the physical and organizational structure of CVU, the participation in daily activities and the casuistry of the clinic’s Imaging Diagnosis Sector. A total of 147 procedures were performed during the Internship: 81 ultrasonography, 60 X-rays, 2 ultrasound guided cystocentesis, 2 ultrasound guided anesthesic blockages and 4 echocardiograms. Of the total number of patients, 91 were canine species, 42 feline species, 1 bovine species and 1 equine species. This report presented the ultrasonographic and radiological approaches in a Multicentric Epitheliotropic Lymphoma case of an 8-year-old Rottweiler dog, which gained prominence in the clinic routine, and highlighted the importance of imaging in the definitive diagnosis of this pathology.